The excitation and detection of Lamb waves in a droplet-loaded plate using air-coupled ultrasonic transducers. (February 2021) - Fan, Zichuan; Zhou, Yang; Wu, Tanghong; Peng, Peng
Highlights: Multiphysics model visualises wave behaviours and interprets inspection signals. Collected signals of leaky Lamb waves are sensitive to size and location of droplets. Lamb wave excitation is impaired by droplets on the test plate surface. Deformed wavefronts of scattered leaky waves lead to attenuation of received signals. Abstract: The signals in an air-coupled ultrasonic inspection system using Lamb waves would be affected by liquid droplets on the surface of test plates. To investigate the wave behaviour, a plate-droplet inspection system comprising a thin isotropic plate loaded with water droplets and a pitch–catch transducer configuration was modelled and studied experimentally. The Lamb waves were generated by a non-contact airborne transmitter. Their energy leaking into the adjacent air was collected by a receiver. To obtain a deep understanding of the effects of water droplets, a multiphysics model based on finite element method was established. The model facilitated the visualization of the wave fields scattered by the droplets on the surface of the plate and evaluated the received signals which were then verified by experimental measurements. This entirely modelling method could be a convenient way to interpret the inspection signals for test plate loaded with liquid droplets.